AB0968 Adrenomedullin Levels in Patients with Familial Mediterranean Fever: A Long Term Follow-Up. (9th June 2015) - Polat, A.; Saglam, C.; Kurt, Y.G.; Basbozkurt, G.; Sozeri, B.; Dursun, I.; Kasapcopur, O.; Peru, H.; Simsek, D.; Gunduz, Z.; Unsal, E.; Gok, F.; et al.
Abstract : Background: Familial Mediterranean Fever (FMF) is the most common periodic fever syndrome, characterized by recurrent fever and serositis attacks. It has been shown that there might be an ongoing subclinical inflammation between attacks. Adrenomedullin (ADM) is synthesized in endothelium, and has been shown to have high levels in patients with inflammation such as FMF. Colchicine is the treatment of choice and given once or twice daily depending on expert opinion. Objectives: In this study, it was aimed to investigate ADM as a marker for inflammation in pediatric patients with FMF who are using colchicine in different dosage schema Methods: Pediatric patients with FMF diagnosed clinically and genetically confirmed were included in the study. The colchicine was started in one or two doses randomly. The clinical and laboratory parameters were assessed on six clinical visits made every two months. After the third visit the dosing schema was changed to twice or once depending on the schema at the beginning. Results: A total of 37 patients (female/male ratio: 0.94) were included in the study. Mean age of patients, age at disease onset, and age at diagnosis were 7.78±2.00, 5.05±3.04, and 7.51±2.66 years, respectively. Twenty patients received colchicine in once daily dosage while 17 patients had in twice-daily dosage at the beginning of the study. There were 10 patients with heterozygote and 27 with homozygote MEFV mutations. After the treatment was started all patients demonstrated improvement in clinical and laboratory findings such as erythrocyte sedimentation rate and C-reactive protein. However, ADM levels did not show any correlation with ESR and CRP levels. Mean ADM levels in six consecutive visits were as follows, first 322.19±161.92 ng/L; second 330.50±189.63 ng/L; third 339.54±168.03 ng/L; forth 378.11±177.63 ng/L; fifth 328.91±172.30 ng/L and sixth 326.25±165.87 ng/L. ADM levels were similar in all visits (p=0.954) and did not show any difference between the first and second three visits i.e. before and after changing the dosage schema (p=0.593). Conclusions: The results indicated that patients using colchicine in once or twice daily doses did not show any significant difference according to the clinical and laboratory findings and had similar effects in controlling disease manifestations. ADM levels did not demonstrate any alterations in all visits that may suggest the continuation of subclinical inflammation in these patients. Disclosure of Interest: None declared